THE INFLUENCE OF ZINC OXIDE NANOPARTICLE ON THE MECHANICAL PROPERTIES OF GRAPHENE OXIDE EPOXY COMPOSITE COATING SYSTEM FOR PIPELINE APPLICATION - KHAIRULANWAR, MOHAMAD KAMAL FIKRIN (2018)
Technology nowadays enable society to venture further into microstructural level from macroscopic to the extent of nanoparticle. This advancement is a gift to enhance more what we have now in our society to the level that initially we can only imagine of. Graphene has caught up many researches interest. Material that we think it is impossible to be one atom thick, light yet it is stronger than steel is now possible. This is possible due to its unique properties that it has. Graphene is sp2-hybradized carbon atoms of monolayer that is bonded in a hexagonal lattice manner. Therefore, it is ultra-thin, that is one atom thick, corrosion resistant due to its stable atom arrangement, chemically inert, mechanically robust, and flexible. That is why with these unique properties, it is aiming to utilize it to the fullest in the oil and gas industry whom must deal with corrosion issues. Total length of pipeline use worldwide can reach millions of kilometres and this pipeline is prone to corrosion which can cost up to billions of dollars annually. With the unique graphene properties, the problem in dealing with corrosion can be minimized and if possible, eliminate entirely. Graphene is utilized to enhance coating that are currently used in the industry that have several drawbacks. Furthermore, graphene on its own have weaknesses. Another material must be introduced to overcome that weakness and the material chosen is zinc. With the laboratory experiment that have been conducted, addition of zinc oxide into graphene oxide epoxy composite shows a significant improvement in the mechanical properties such as an increase of 60% in tensile strength when compared to graphene oxide epoxy composite without the presence of zinc oxide. However, certain percentage addition of zinc oxide such as at 0.5 and 0.1% can cause dramatically decrease in the mechanical properties due to crowding effect.